Ferlismat á nýju kynfræðsluefni fyrir unglinga - Sóley S. Bender (Félag íslenskra hjúkrunarfræðinga, 2012)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn View/Open Allur texti - Full text Active participation of adolescents in the development of a sexuality education program is recommended. Such an approach is important to make a program more suitable for this age group. The purpose of this research project was to pilot test a new sexuality education program for adolescents and explore the costs and benefits of its implementation. A new sexuality education curriculum of eight lessons was pilot tested in six classes among eight grade students within one primary school in Reykjavík in the fall of 2010. Seven graduate students at the University of Iceland taught the lessons along with the author. Process evaluation was performed in order to find out how the teaching proceeded. This evaluation was based on an overall evaluation of each lesson and its parts as well as written outcomes of the exercises by the students. The results showed great interest among the students in the subject and they were participating actively in the group exercises most of the time. Generally the teaching went well but the teachers found the group exercises time consuming. In total 87% of the group exercises and all of the evaluated transparencies received very good or good scores. The group exercises created many good ideas among the students which demonstrated their good understanding of the content. In the end of the teaching the students had grasped the holistic view of sexual and reproductive health. The group exercises were pedagogically demanding and it is therefore important to be trained in group work before teaching this curriculum. The program is promising for further testing in some schools after taking the recommended changes of this pilot test into consideration Við þróun kynfræðslunámsefnis fyrir unglinga er mælt með því að þeir séu virkir þátttakendur í ferlinu og er það talið mikilvægt til þess að námsefnið nái betur til þessa aldurshóps. Tilgangur þessarar rannsóknar var að forprófa ...